The Interface Design Of Web-Based Interactive Catalog In Bandungrejosari Ward Malang City - Evy Poerbaningtyas; Ana Utami Nur Rahman; Adita Ayu Kusumasari (IC-ITECHS, 2022)
MSMEs (Micro, Small and Medium Enterprises) are one of the foundations of the Indonesian economy that was able to survive the monetary crisis that hit from 1997 to 1998. in 2012 and increased to 62.9 million MSME businesses including UMKM in the Malang city area (BPS, 2017) (Depkop, 2018) (YR Suci, 2017). As technology develops, SMEs are starting to take advantage of the internet network through e- commerce websites and social media as a means of buying and selling online. With this development, competition between businesses is getting tighter and more competitive. So that many of the same products can be found with different sellers and prices. The impact that arises from this intense competition is the development of the same product so that it does not highlight the main products of these MSMEs and only focuses on selling trending products. Based on the problems found, the Bandungrejosari Village, Malang City, requires accurate information facilities as a reference for developing information updates in the MSME sector digitally in the form of a website. Media Website was chosen because it can display information quickly and in real-time. With the existence of the Kata UMKM Website, it is hoped that it can expand MSME information in the Bandungrejosari sub- district, so that it is better known, especially for the people of the Bandungrejosari sub-district and Malang City.